Exploiting a multicomponent domino reaction strategy for the tailoring of versatile environmentally sensitive fluorophore-based nicotinonitriles incorporating pyrene and fluorene moieties. Issue 68 (3rd December 2019) - Hussein, Essam M.; El Guesmi, Nizar; Ahmed, Saleh A.
Abstract : A simplistic and highly effective protocol for the synthesis of a new class of poly-functionalized innovative nicotinonitriles incorporating pyrene and/or fluorene moieties has been developed through the domino four-component condensation reaction. Abstract : A simplistic and highly effective protocol for the synthesis of a new class of poly-functionalized innovative nicotinonitriles incorporating pyrene and/or fluorene moieties has been developed through the domino four-component condensation reaction of 1-(pyren-1-yl)ethanone/1-(9 H -fluoren-2-yl)ethanone, numerous aromatic aldehydes, and 3-oxo-3-(pyren-1-yl)propanenitrile/3-(9 H -fluoren-2-yl)-3-oxopropanenitrile and ammonium acetate in acetic acid as a reaction medium. The advantages of this approach are the short reaction time, excellent yield, and the easy experimental workup that affords substrate diversity and operative competence under metal-free reaction conditions for the formation of C–C and C–N bonds. The substituent effects on the photophysical property-based absorption and the emission of the synthesized compounds in dichloromethane have been well-investigated. Strong absorption quenching of around 100 nm was observed when substitution of the benzene ring at the C4 -position of the pyridine moiety occurred with an electron-donating (–N(CH3 )2 ) group. All of the newly synthesized nicotinonitrile derivatives showed strong blue-green fluorescence emission with maxima in the range between 420–630 nm. These highly pronounced emission spectra will help this family of compounds to find application in many areas and the field of materials science.